Experimental re-evaluation of flunarizine as add-on antiepileptic therapy - Anamika Thakur (Journal of Pharmacy and Bioallied Sciences, 2011)
Background: Experimental studies have found several calcium channel blockers with anticonvulsant property. Flunarizine is one of the most potent calcium channel blockers, which has shown anticonvulsant effect against pentylenetetrazole (PTZ) and maximal electroshock (MES)-induced seizures. However, further experimental and clinical trials have shown varied results. We conducted a PTZ model experimental study to re-evaluate the potential of flunarizine for add-on therapy in the management of refractory epilepsy. Materials and Methods: Experiments were conducted in PTZ model involving Swiss strain mice. Doses producing seizures in 50% and 99% mice, i.e. CD 50 and CD 99 values of PTZ were obtained from the dose-response study. Animals received graded, single dose of sodium valproate (100-300 mg/kg), lamotrigine (3-12 mg/kg) and flunarizine (5-20 mg/kg), and then each group of mice was injected with CD 99 dose of PTZ (65mg/kg i.p.). Another group of mice received single ED 50 dose (dose producing seizure protection in 50% mice) of sodium valproate and flunarizine separately in left and right side of abdomen. Results were analysed by Kruskal-Wallis ANOVA on Ranks test. Results: As compared to control, sodium valproate at 250 mg/kg and 300 mg/kg produced statistical significant seizure protection. At none of the pre-treatment dose levels of lamotrigine, the seizure score with PTZ differed significantly from that observed in the vehicle-treated group. Pre-treatment with flunarizine demonstrated dose-dependent decrease in the seizure score to PTZ administration. As compared to control group, flunarizine at 20 mg/kg produced statistical significant seizure protection. Conclusion: As combined use of sodium valproate and flunarizine has shown significant seizure protection in PTZ model, flunarizine has a potential for add-on therapy in refractory cases of partial seizures. It is therefore, we conclude that further experimental studies and multicenter clinical trials involving large sample size are needed to establish flunarizine as add-on therapy in refractory epilepsy.